c y ABDULMAJID A. ZANDANI ; Translated by: Chafik Abdelghani (PhD) ; Cover design by : Sarah Berkani - Zandani, Abdul Majid A.; Abdelghani, Chafik; Berkani, Sarah (London : Al-Firdous Ltd., 2008)
Islam teaches us how to have patience in ease and in hardship and to maintain good manners even with those who are rude and harsh, this Islamic book by Amr Khalid explained how to persevere and maintain an Islamic personality and etiquette and the reward for doing so. Sabr (Patience) Dhawq (Good Manners) Al-Eether (Noble)
Keywords: Faith (Islam); God (Islam)